Keterbatasan Sarana dan Prasarana SLB, Hambatan dalam Pendidikan - Agus Sibagariang; Abellia Najwa Nabila; Fatma Nabila; Fatri Elina Sigiro; Feffiola Destiana Margaretha Pakpahan; Mazidah Zahra Ramadani Br. Limbong; Saneta Sinurat; Anggia Puteri; Lili Tansliova (Universitas Serambi Mekkah, 2025)
The limited facilities and infrastructure in Special Needs Schools (SLB) are one of the main challenges in providing access to proper education for Children with Special Needs (ABK). This study aims to analyze various obstacles to facilities and infrastructure that are obstacles in the implementation of education in Special Needs Schools (SLB) that are in accordance with their needs. The method used by researchers in gathering this information is a literature study by collecting and analyzing data from various previous studies related to inclusive education and the condition of facilities and infrastructure in SLB. The results obtained indicate that there are many limitations to facilities and infrastructure that are obstacles in ABK education, ranging from limited infrastructure, minimal accessibility facilities, and the lack of educators who have special competencies that are obstacles in education for ABK. Therefore, more systematic interventions and policy efforts are needed to improve the quality of facilities and infrastructure in SLB so that education for ABK can run optimally.